Al-Ma‘ahid al-Turāthīyah wa Shuyū‘īyah wa al- Ṭuruq al-Ṣūfīyah - Anwar, Khoirul (Studia Islamika, 1998)
This paper will reveal images Pesantren tradition, Kyai, and the congregation that has not been studied by scholars such as van den Berg, Hurgronje, and Clifford Geertz thus able to capture the real power of intellectual tradition and religious boarding schools. Kyai (charismatic religious teachers/scholars) and pesantren (traditional Islamic boarding schools owned and run by kyai) have become common subjects of research among scholars studying Islam in Indonesia.DOI: 10.15408/sdi.v5i1.761